2012
DOI: 10.1021/cs300234e
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effect of Carbon Nanotubes: Copper Nanoparticles Filled Carbon Nanotubes for Hydrogenation of Methyl Acetate

Abstract: Copper nanoparticles filled carbon nanotubes (CNTs) with varied tube diameters were prepared via a convenient sonication-assisted impregnation approach. CNTs and Cu nanoparticles filled CNTs were thoroughly investigated using transmission electron microscopy, Raman spectroscopy, N 2 adsorption, X-ray diffraction, and H 2 temperature programmed reduction. Confinement effects of CNTs, originated from its diameter and microstructure, on the filled Cu nanoparticles were discovered. For CNTs with smaller tube diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 56 publications
4
91
1
Order By: Relevance
“…35, 48, H 2 -TPR profiles of CuO-CeO 2 (r)/CNT catalysts:The above assignment of reduction peaks is mainly from the point of view of the copper oxides dispersion and interaction between copper oxides and ceria. Nevertheless, the effect of support should also be taken into consideration in the case of supported CuO-CeO 2 system since the facilitated reduction of CuO due to the promoted electron transfer by CNT as previously reported,65,70 which is witnessed by the comparison of TPR profiles between CuOCeO 2 (5/5)/CNT and those supported on AC, Al 2 O 3 and SiO 2 (shown as supplementary data)…”
mentioning
confidence: 87%
“…35, 48, H 2 -TPR profiles of CuO-CeO 2 (r)/CNT catalysts:The above assignment of reduction peaks is mainly from the point of view of the copper oxides dispersion and interaction between copper oxides and ceria. Nevertheless, the effect of support should also be taken into consideration in the case of supported CuO-CeO 2 system since the facilitated reduction of CuO due to the promoted electron transfer by CNT as previously reported,65,70 which is witnessed by the comparison of TPR profiles between CuOCeO 2 (5/5)/CNT and those supported on AC, Al 2 O 3 and SiO 2 (shown as supplementary data)…”
mentioning
confidence: 87%
“…Indeed, the calculated turnover frequency (TOF) for gold nanoparticles in the hydrogenation of cinnamaldehyde was reported to increase 90-fold upon confinement within MWCNT, despite only 40% of AuNP estimated to be encapsulated. 51 These examples of methyl acetate and cinnamaldehyde hydrogenation within narrow MWCNT and SWCNT respectively demonstrate the concept that greater confinement effects may be possible within narrower CNT, with the potential drawback of reduced diffusion relative to wider CNT. The authors appraised the influences of nanoscale confinement, the impregnation procedure and hightemperature annealing on the yields and distributions of products across a range of hydrogenation reactions.…”
Section: Hydrogenationmentioning
confidence: 86%
“…46,47 Along with these remarkable changes to selectivity, almost all confined catalysts described showed enhanced activity as a consequence of nanoscale confinement. 51,52 Interestingly, MWCNT of internal diameter 7 (AE3) nm and 25 (AE5) nm were compared and the highest conversion values were observed within the narrower CNT. 48 Rong et al recently explored the ruthenium nanoparticlecatalysed hydrogenation of benzene, p-chloronitrobenzene and cinnamaldehyde in MWCNT.…”
Section: Hydrogenationmentioning
confidence: 99%
“…For example, Bao et al found that encapsulation interactions of CNT could not only reduce the size of Pt nanoparticles, but also prefer the Pt species at active reduced states [14]. In addition, the metal NPs (i.e., Pd, Rh, Fe, Ru and so on) encapsulated inside the nanotube could deliver enhanced catalytic activity or higher enantioselectivity towards a wide range of reactions, such as oxygen reduction reaction (ORR) [15], Fisher-Tropsch synthesis (FTS) reaction [16][17][18] and liquid phase hydrogenation reaction [19][20][21]. As illustrated, the confining metal or metal oxide nanoparticles inside CNTs often lead to a different catalytic activity with respect to the same particles deposited on the external surfaces.…”
Section: Introductionmentioning
confidence: 99%